Precipitation collection and evapo(transpi)ration of living wall systems: A comparative study between a panel system and a planter box system. (December 2017) - van de Wouw, P.M.F.; Ros, E.J.M.; Brouwers, H.J.H.
Abstract: By reducing the quantity of precipitation reaching the ground, a green façade can contribute to a more natural way of rainwater drainage. Additionally, it provides shadowing, insulation, and evapotranspiration (ET) of water enabling it to reduce the heat load of a building. The collection of precipitation and the ET were tested over a two month period on two commercially available living wall systems. The entering and outgoing amounts of water were monitored, as well as the mass variation of the systems. The weather data, collection of precipitation and condensation, and the ET were determined. The precipitation collection of one vertical m 2 expressed as an equivalent percentage of the precipitation on one horizontal m 2 results on average in 18.8% and 33.0% for the panel and the planter box system respectively, whereby the occurrence of wind driven rain is not essential. Wind speed, humidity, air temperature, and solar radiation have been found to be neither independent nor dominant, yet trends for both systems are in good correlation. Correlating the measured ET with the reference ET obtained through the FAO-56 Penman-Monteith equation results in a factor of 1.46 and 0.76 between a horizontal m 2 of reference crop and a vertical m 2 of the panel and the planter box system respectively, values relating to deviating designs and dissimilar irrigation procedures. The total estimated ET power is 18 (±3) kW/m 2 /year and 11 (±3) kW/m 2 /year for the panel and the planter box system, respectively. The derived water balances indicate the need for proper irrigation management throughout the year. Highlights: Collecting and buffering of rain relate to occurring conditions and system design. Evapo(transpi)ration relates to weather conditions, design, and irrigation. Living wall systems evapo(transpi)rative cooling activates when cooling is desired. Water balance and prognosis indicate the need for continuous irrigation management.